Cefquinome-loaded microsphere formulations against Klebsiella pneumonia infection during experimental infections - Shaoqi Qu; Cunchun Dai; Jiajia Zhu; Li Zhao; Yuwen Li; Zhihui Hao (Taylor & Francis Group, 2018)
The aim of this study was to prepare cefquinome-loaded polylactic acid microspheres and to evaluate their in vitro and in vivo characteristics and pharmacodynamics for the therapy of pneumonia in a rat model. Microspheres were prepared using a 0.7 mm two-fluid nozzle spray drier in one step resulting in spherical and smooth microspheres of uniform size (9.8 ± 3.6 μm). The encapsulation efficiency and drug loading of cefquinome were 91.6 ± 2.6% and 18.7 ± 1.2%, respectively. In vitro release of cefquinome from the microspheres was sustained for 36 h. Cefquinome-loaded polylactic acid microspheres as a drug delivery system was successful for clearing experimental Klebsiella pneumonia lung infections. A decrease in inflammatory cells and an inhibition of inflammatory cytokines TNF-α, IL-1β and IL-8 after microspheres treatment was found. Changes in cytokine levels and types are secondary manifestations of drug bactericidal effects. Rats were considered to be microbiologically cured because the bacterial load was less than 100 CFU/g. These results also indicated that the spray-drying method of loading therapeutic drug into polylactic acid microspheres is a straightforward and safe method for lung-targeting therapy in animals.